Chirped periodic and localized waves in a weakly nonlocal media with cubic-quintic nonlinearity. (December 2021) - Triki, Houria; Kruglov, Vladimir I.
Highlights: A wide variety of periodic waves have been found for the first time. The chirped solitary wave solutions of NLS with weak nonlocality are found. The self-similar light propagation in an inhomogeneous nonlocal media is given. Abstract: We study the propagation of one-dimentional optical beams in a weakly nonlocal medium exhibiting cubic-quintic nonlinearity. A nonlinear equation governing the evolution of the beam intensity in the nonlocal medium allows us to examine whether the traveling-waves exist in such optical material. An efficient transformation is applied to obtain explicit solutions of the envelope model equation in the presence of all material parameters. We find that a variety of periodic waves accompanied with a nonlinear chirp do exist in the system in the presence of the weak nonlocality. Chirped localized intensity dips on a continuous-wave background as well as solitary waves of the bright and dark types are obtained in a long wave limit. A class of propagating chirped self-similar solitary beams is also identified in the material with the consideration of the inhomogeneities of media. The applications of the obtained self-similar structures are discussed by considering a periodic distributed amplification system.